The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41409-020-01031-w
|View full text |Cite
|
Sign up to set email alerts
|

1,25-dihydroxyvitamin-D3 but not the clinically applied marker 25-hydroxyvitamin-D3 predicts survival after stem cell transplantation

Abstract: The serum level of 25-hydroxyvitamin-D3 is accepted as marker for a person’s vitamin D status but its role for the outcome of allogeneic hematopoietic stem cell transplantation (HSCT) is controversially discussed. The impact of 1,25-dihydroxyvitamin-D3 on HSCT outcome, however, has never been studied. In a discovery cohort of 143 HSCT patients we repeatedly (day −16 to 100) measured 1,25-dihydroxyvitamin-D3 and in comparison the well-established marker for serum vitamin D status 25-hydroxyvitamin-D3. Only lowe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 94 publications
1
16
0
Order By: Relevance
“…Analysing a discovery cohort consisting of 143 HSCT patients, our data highlight peri-transplant (day −2 to 7), 1,25-dihydroxyvitamin D3 levels, but not the commonly monitored 25-hydroxyvitamin D3 levels, as potent predictor of 1-year transplant-related mortality (TRM). This finding was further confirmed by analysing three additional cohorts, consisting altogether of 365 patients and suggest to monitor both vitamin D3 metabolites in HSCT patients ( 10 ).…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…Analysing a discovery cohort consisting of 143 HSCT patients, our data highlight peri-transplant (day −2 to 7), 1,25-dihydroxyvitamin D3 levels, but not the commonly monitored 25-hydroxyvitamin D3 levels, as potent predictor of 1-year transplant-related mortality (TRM). This finding was further confirmed by analysing three additional cohorts, consisting altogether of 365 patients and suggest to monitor both vitamin D3 metabolites in HSCT patients ( 10 ).…”
Section: Introductionmentioning
confidence: 59%
“…Although several studies addressed the importance of 25hydroxyvitamin D3 serum levels in the context of HSCT, little is known about the active 1,25-dihydroxyvitamin D3 metabolite. We previously demonstrated that peri-transplant 1,25-dihydroxyvitamin D3 levels were the only significant independent predictor for oneyear-survival besides severe aGvHD (10). Nevertheless, why patients with high 1,25-dihydroxyvitamin-D3 levels are at less risk for TRM than those with low levels remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conflicting data about effect of vitamin D on transplant outcomes shown in several studies quoted above are hard to explain. However, Peter et al studied the effect of 1,25 dihydroxyvitamin D3 and 25 OH vitamin D3 in 143 adults patients undergoing allogenic HSCT and showed that only lower 1,25‐dihydroxyvitamin‐D3 levels around HSCT (days −2 to 7, peri‐transplant) were significantly associated with higher 1‐year TRM risk (Mann‐Whitney U test, p = .001) 17 . This was confirmed by Cox‐model regression without and with adjustment for baseline risk factors and severe acute GvHD (unadjusted p = .001 and adjusted p = .005).…”
Section: Discussionmentioning
confidence: 99%